2015
DOI: 10.1186/s11671-015-1158-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteins Enhance Dispersion Stability and Influence the Cytotoxicity and Dosimetry of ZnO Nanoparticles in Suspension and Adherent Cancer Cell Models

Abstract: Agglomeration and sedimentation of nanoparticles (NPs) within biological solutions is a major limitation in their use in many downstream applications. It has been proposed that serum proteins associate with the NP surface to form a protein corona that limits agglomeration and sedimentation. Here, we investigate the effect of fetal bovine serum (FBS) proteins on the dispersion stability, dosimetry, and NP-induced cytotoxicity of cationic zinc oxide nanoparticles (nZnO) synthesized via forced hydrolysis with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…In particular, NPs–protein corona formation has been well reported to affect cellular responses. For example, it was reported that the ZnO NPs–serum protein interaction influences cytotoxicity, showing lower or higher cytotoxicity when NPs were dispersed in serum proteins [ 11 , 15 , 16 ]. The aggregation of di-block copolymer NPs was found to be induced by fibrinogen, while the adsorption of albumin and complement component 3 (C3) protein on the surface of NPs triggered the activation of the immune complement cascade [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NPs–protein corona formation has been well reported to affect cellular responses. For example, it was reported that the ZnO NPs–serum protein interaction influences cytotoxicity, showing lower or higher cytotoxicity when NPs were dispersed in serum proteins [ 11 , 15 , 16 ]. The aggregation of di-block copolymer NPs was found to be induced by fibrinogen, while the adsorption of albumin and complement component 3 (C3) protein on the surface of NPs triggered the activation of the immune complement cascade [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the biocompatibility, other fascinating properties of ZnO nanoparticles such as wide band gap, high exciting binding energy, and quantum effects may also support to make it an ideal candidate for improving the stability of cellulase enzyme. Moreover, since the hexagonal wurtzite structure of ZnO nanoparticles is thermodynamically stable, it may be helpful to influence the thermal stability of crude cellulase enzymes ( Ashrafi and Jagadish, 2007 ; Anders et al, 2015 ). Thus, use of such type of thermally stable ZnO nanoparticles treated cellulase can improve the economics of market involved in the enzyme-based hydrolysis of biomass, because the enzymatic degradation of cellulose needs the high enzyme loading which increases the production cost as well as economic demands.…”
Section: Resultsmentioning
confidence: 99%
“…[49,[122][123][124] Compared with water and neutral pH conditions, particle dissolution rates may speed up in acidic conditions as well as cell culture media. [49,125] Salts, vitamins, amino acids, peptides, and proteins that present in biological media can coordinate with the metal ions, and thus promote the dissolution process. Due to the large surface-to-volume ratio of ENMs, substantial defects on NP surfaces may also facilitate the dissolution process and the released ions may eventually reach to a homeostasis with particle aggregates.…”
Section: Decompositionmentioning
confidence: 99%